(untitled) (Revista do Tribunal Regional Federal da 3ª Região, 2019)
The purpose of this presentation is to consider the influence of economic arguments on the analysis of court cases, their repercussions on legal reasoning, through the necessary intertwining of economics and law. The aim is to reflect faithfully on the pragmatic experience of judicial decisions, their foundations and axiological lines, in order to show the influence determined by the foundations of economics by the foundations of economics, based on the concept of economic utility in the legal system. We can therefore see the epistemological option outlined in this work to examine the interaction between Law and Economics, under a macro analysis of the phenomenon, in order to give a better view of interpretation, both in terms of its origins and limits, as well as its consequences - without detracting from the magnitude of Economics in the realization of Law. The article seeks to take stock of the different discussions erected in the national and international spheres of modern interdisciplinary study of both branches of science: human/political on the one hand; and macroeconomics, seen in terms of its application of economic method and reasoning on the other, in order to emphasize the economic argument in court, situating the issue within constitutional interpretation.